Metal-Free Synthesis of 2,4,6-Trisubstituted Pyridines via Iodine-Initiated Reaction of Methyl Aryl Ketones with Amines under Neat Heating - Xu, Hui; Zeng, Ji-Chao; Wang, Fang-Jian; Zhang, Ze (Synthesis, 2017)
A neat heating protocol has been developed for metal-free synthesis of various 2,4,6-trisubstituted pyridines via iodine-initiated (in situ generated HI-catalyzed) condensation of methyl aryl ketones with amines and the following cyclization-aerobic oxidation. Large-scale synthesis and mechanistic investigation were also performed.
Keywords: 2,4,6-trisubstituted pyridine; molecular iodine; metal-free; neat heating; methyl aryl ketone